Critical Raw Materials in the European Union: Swedish Stakeholders’ and Sámi Interests in the European Commission’s Consultation on a Critical Raw Materials Acts ... - Knochelmann, Anita (The University of North Carolina at Chapel Hill University Libraries, 2024)
This thesis examines the interests of Swedish stakeholders in the context of the European Commission’s proposed Critical Raw Materials (CRM) Act, with a particular focus on how Sámi interests are considered by these stakeholders. The research problem is centred on the juxtaposition between the need to extract resources crucial for the Green Transition of the European Union on the one hand and the protection of Indigenous ways of life in mining areas on the other. The research questions investigate how Swedish stakeholders engage with the consultation process, the specific interests they express in relation to the CRM Act, and whether they consider the interests of the Sámi People. To address these questions, this thesis employs qualitative content analysis, which enables an in-depth examination of diverse forms of communication, including written statements and interviews. The analytical framework is constructed through inductive coding of the collected material. The data set comprises six written responses ...